THE EFFECT OF LEADERSHIP STYLE, WORK MOTIVATION ON JOB SATISFACTION OF STATE CIVIL APPARATUS IN THEREGIONAL SECRETARIAT OF GORONTALO REGENCY: Doi: https://doi.org/10.47918/jhts.v3i1.334 - Sutrisno Luma; Ayu Anastasya Rachman; Lisda Van Gobel (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This research is descriptive quantitative and aims to determine and analyze (1) the influence of leadership style on job satisfaction of the State Civil Apparatus (ASN) at the Regional Secretariat of Gorontalo Regency; (2) The effect of work motivation on job satisfaction of State Civil Apparatus (ASN) at the Regional Secretariat of Gorontalo Regency; (3) The influence of leadership style, work motivation on job satisfaction of State Civil Apparatus (ASN) at the Regional Secretariat of Gorontalo Regency. provides opportunities for employees to advance, work motivation has an influence weak but positive on employee job satisfaction by 0.147 or 14.7 percent, due to lack of opportunities for advancement, low job performance, lack of responsibility; (3) Leadership style (X1) and work motivation (X2) simultaneously have a strong and positive influence on job satisfaction (Y). It is suggested that participative leadership style is needed effectively for its employees, considering that this variable has a strong influence on employee job satisfaction.